The effect of crop insurance on the financial risk of smallholder rice farmers in Cameroon - Litika, Geraldine; Aloysius, Njong Mom; Fonchamnyo, Dobdinga Cletus (International Journal of Social and Administrative Sciences, 2024)
This study examined the effect of crop insurance on the financial risk of smallholder rice farmers in the grass field of Cameroon. Panel data from 76 Smallholder rice farming groups from 2019-2022 was used, while the Panel-corrected standard error technique was used for estimation. The results revealed that crop insurance captured using inputs (fertilizers, herbicides, and treated seeds) and land preparation had a positive and statistically significant effect on financial risk. These results validate the risk balancing hypothesis for smallholder rice farmers. Control variables like Farm size and labour had a positive and statistically significant effect, while training cost and buying price had a negative and statistically significant effect on financial risk. The results therefore, indicate that smallholder rice farmers need to adopt crop insurance practices such as use of quality farm inputs and better land preparation techniques in order to manage financial risk.